Correlaciones a partir de la Intensidad de Arias para datos acelerográficos de Costa Rica - Schmidt Díaz, Víctor (Universidad de Costa Rica, 2007)
This research purposes the use of the Arias Intensity (IA) index as an indicator of the strength of an earthquake, which can be correlated with other seismic parameters as the moment magnitude (Mw), hypocentral distance (D), peak ground acceleration (PGA), geotechnical conditions of the stations (S) and the Modified Mercalli Intensity scale (IMM) assigned to each site after the occurrence of an earthquake. The original database consists in 1018 free field strong motion records obtained between 1983 and 2006 by the Earthquake Engineering Laboratory of the University of Costa Rica and the Costa Rican Institute of Electricity. After defining some selection criteria, the amount of records diminished to 734 which come from 320 felt earthquakes. The correlations obtained after several tests are: IA = 8E-6*(PGA)1,9956 , r2 = 0,923, Ln(IA) = -13,799+2,685*Mw-1,611*Ln(D)-0,0034*D+0,945*S, r2 = 0,71.IMM = 0,5719*Ln(IA)+7,1952 , r2 = 0,9905. Results show high correlation coefficient for every regression, as well as similar behavior in some cases considering the ones proposed by authors using different worldwide databases. Keywords: Arias and Mercalli intensities, regressions, accelerograms, Costa Rica.